Perception of university lecturers on the reasons young adults abuse drugs in Nnamdi Azikiwe University, Awka - Apiti, A. A. (Journal of Research in Adult and Continuing Education, 2023)
The paper investigated the perceptions of University lecturers on the rising habit of drug abuse among young adults in Nnamdi Azikiwe University, Awka. The paper adopted a descriptive survey research design. The population of the study comprised 2,643 teaching staff in Nnamdi Azikiwe University, Awka. A taro yamane formula was used to get a representative sample size of 347 lecturers. Simple random sampling technique was used to select the sample size across the 14 faculties in Nnamdi Azikiwe University, Awka. Questionnaire was the instrument for data collection. The instrument was dully validated. Data collected was analyzed using mean scores to determine the respondents’ level of agreement to each item of the research question. Based on the findings of the study, it was discovered that young adults abuse drug because of its availability, peer pressure, academic stress, anxiety, ignorance influence of media, and insufficient parental guidance. The researcher based on the study gave the following recommendations: the school management and the government of Anambra state should embark on aggressive annihilation of the sources of illicit drug in Nnamdi Azikiwe University Awka, the lecturers in Nnamdi Azikiwe University, Awka should be agents of change by involving themselves highly in sensitization of young adults on the harmful effects of drug abuse, the school management should reduce the pressure on academic activities by increasing the span of study per semester, among others.
Keywords: Perception; Drug Abuse; Young Adults